Existentia Africana : Understanding Africana Existential Thought. - Gordon, Lewis R. (Africana thought., 2000)
Lewis R. Gordon introduces and discusses Africana existential thought, covering a wide range of both classic and contemporary thinkers - from Frederick Douglass and W.E.B. Dubois to Frantz Fanon, Angela Davis and Naomi Zack.